Modified decompression technique in the management of odontogenic cystic lesions: An retrospective study - Pavan K Batchu; Tapas K Bandyopadhyay; Vuyyuru V Devi; A Mukundapriya (Wolters Kluwer Medknow Publications, 2023)
Introduction: Odontogenic cystic lesions requiring conservative management were treated with a novel technique of modified decompression and assessed. Aims and Objective: This study aimed to evaluate the resolution of the lesion, recurrence, and complications in patients treated with the novel modified decompression technique. Materials and Methods: The retrospective study included patients treated with the novel modified decompression technique between 2004 and 2022. The cystic lesions were packed with chlorhexidine acetate gauze dressing (Bactigras), and patients were prescribed a combination of Calcium, Vitamin C, and Vitamin D. Pack was changed periodically until a reduction of at least 80% in the volume of the lesion was achieved. Period of decompression, volume at each follow-up, and lesion size were recorded. In addition, inter-group significance co-relating the size and diagnosis of the lesions with the rate and duration of healing were derived by ANOVA test. Results: OKC, unicystic ameloblastoma, and dentigerous cysts were included, and the follow-up period ranged from one year to eighteen years. 25 cases (83.33%) showed full resolution, whereas five cases (16.17%) showed more than 80% resolution. The period of decompression and the rate of decompression was found to correlate with both the diagnosis and the size of the lesion. Conclusions: The modified decompression technique is superior to traditional decompression with a high rate of resolution of cystic lesions and no recurrence over a long follow-up period.